2020
DOI: 10.21203/rs.3.rs-15489/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Assessing immune infiltration and the tumor microenvironment for the diagnosis and prognosis of sarcoma

Abstract: Background: Sarcomas, cancers originating from mesenchymal cells, are comprehensive tumors with poor prognoses, yet their tumorigenic mechanisms are largely unknown. In this study, we characterize infiltrating immune cells and analyze immune scores to identify the molecular mechanism of immunologic response to sarcomas.Method: The “CIBERSORT” algorithm was used to calculate the amount of L22 immune cell infiltration in sarcomas. Then, the “ESTIMATE” algorithm was used to assess the “Estimate,” “Immune,” and “S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…There was a strong correlation with the CIBERSORTx 'M0 macrophage' signature and 'Macrophage' xCell signature, both of which are derived from the Immune Response In Silico (IRIS) gene expression dataset for macrophages after 7 days of differentiation from monocytes [23][24][25] . The CIBERSORTx M0 macrophage gene signature has been more recently associated with tumor promotion and poor prognosis in multiple cancers [11][12][13][14][15] but it is unclear if the M0 signature is describing a distinct population of macrophages or (more likely) multiple populations of macrophages which do not fit well with classical and non-classical macrophage signatures. The M0 population has been previously reported in murine HGSOC mouse models 26 , however, this is the first observation of M0 macrophages within the TME of patients with HGSOC.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a strong correlation with the CIBERSORTx 'M0 macrophage' signature and 'Macrophage' xCell signature, both of which are derived from the Immune Response In Silico (IRIS) gene expression dataset for macrophages after 7 days of differentiation from monocytes [23][24][25] . The CIBERSORTx M0 macrophage gene signature has been more recently associated with tumor promotion and poor prognosis in multiple cancers [11][12][13][14][15] but it is unclear if the M0 signature is describing a distinct population of macrophages or (more likely) multiple populations of macrophages which do not fit well with classical and non-classical macrophage signatures. The M0 population has been previously reported in murine HGSOC mouse models 26 , however, this is the first observation of M0 macrophages within the TME of patients with HGSOC.…”
Section: Resultsmentioning
confidence: 99%
“…These macrophages were characterized by the gene signature for M0 macrophages that are used in CIBERSORTx and xCell. Originally the signature for M0 macrophages was used to define a non-activated macrophage phenotype, however more recent studies indicate that the signature is also a feature of a poorly characterized macrophage population that associates with poor prognosis in hepatocellular 11 , sarcoma 12 , breast 13,14 , and lung 15 cancers. TAMs likely exist as a spectrum of subtypes influenced by their interaction with malignant and immune cells and secreted factors during infiltration into the tumor tissue 16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Human sarcomas are generally considered immunologically "cold" and contain lower levels of intratumoral lymphocytes than epithelial-derived malignancies such as breast cancer, colon cancer, or renal cell carcinoma (55). They also have low mutational burdens (56) and their intratumoral immune landscape is dominated by tumor associated macrophages (57). Multiple studies have demonstrated the ineffectiveness of immunotherapies in treating a variety of sarcoma subtypes (58)(59)(60)(61)(62), further supporting the idea that tumors of mesenchymal origin contain unique barriers to immunomodulation.…”
Section: ) Including the Induction Of Regulatory T Cells (Tregs) And ...mentioning
confidence: 99%
“…M1 macrophage infiltration promotes an inflammatory microenvironment by increasing the expression of IL-1, IL-6 and IL-12, and M2 macrophage infiltration promotes inflammatory escape by increasing the expression of PD-L1 and IL-10 [47,48]. A previous study suggested that patients with a higher infiltration of CD8+ T cells and M1 macrophages in the TME have a better prognosis and high immune checkpoint gene expression than those infiltrated by M0/2 macrophages [22,49]. In our results, the microenvironment of the CCA high-risk group had significantly enriched M0 macrophage infiltration.…”
Section: Five Of Those Nine Prognostic Genes (Hells Hoxc6 Mfsd2a Otx1...mentioning
confidence: 99%